Corrosion Resistance Evaluation of Aluminum 6013 Metal Matrix Composites Reinforced with Red Mud Particulates in Acid Chloride Medium - Chandrashekara, K. N. (Recent Developments in Chemistry and Biochemistry Research Vol. 1, 2024)
This study focuses on assessing the corrosion properties of metal matrix composites comprised of red mud particulate and aluminum 6013 alloy, particularly for potential use in automobiles due to their cost-effectiveness and comparable or superior performance. Limited research has been conducted on the environmental behaviour of these alloys. Aluminum 6013 alloys, chosen for their relatively high strength in comparison to zinc alloys with a lower melting point, serve as the matrix alloy in this research. Red mud, known for its ceramic inertness and resistance to acidic mediums, is used as a reinforcement in particle sizes ranging from 50-80 µ. Corrosion rates are determined through experiments in an acid chloride medium using the static weight loss method. The metal matrix composites, prepared according to ASTM standards via the liquid melt metallurgy technique using the vortex method, include variations with 2%, 4%, and 6% by weight of red mud, alongside an unreinforced matrix. Tests are conducted using different concentrations of hydrochloric acid at room temperature, with specimens in the form of 20 mm × 20 mm cylinders. Scanning electron microscopy is employed to examine the microstructures of the specimens. Corrosion rates for all samples are calculated using the formula 534 W/DAT mpy. Results, presented in simulation curves, indicate that the composite exhibits higher corrosion resistance compared to the matrix alloy. However, in each test, both alloy composites show a decrease in corrosion resistance over time, attributed to the physical barrier formed by the red mud particles.